Década dourada: mapeamento e analise dos cartazes cubanos para o cinema estrangeiro (1960- 1969) - Oliveira, Leila Kelly Gualandi (2019)
The creation of the Cuban Institute of Cinematographic Art and Industry (Icaic) warmed up and renewed the production of cinema and serigraphy, beginning with the Socialist Revolution in 1959. Cuba was about to enter a period of not only political and social renewal, but also cultural. The posters, already perceived as an important tool of mass communication in other totalitarian regimes, served the Caribbean country for two purposes: a political and a cultural one; and to promote the new regime and as a mechanism for the propagation of cultural programs. This research intends to understand the environment that the Cuban poster creates and that results from it, besides observing the relations between public and poster, seeking to assimilate how a mass communication tool might have become something so valuable for the art of a country where advertising was no longer understood in the same way. The object of study of this research is the production of Cuban serigraphic posters produced for the dissemination of foreign film productions between the years 1960 and 1969. Six countries were thus chosen - Germany, Brazil, Czechoslovakia, Japan, Poland and Soviet Union -, with the intention of creating a parallel between the Cuban posters and the foreign ones. To do so, it became necessary to catalog the posters, applying filters where, by elimination, the corpus resulted in thirty foreign copies and, consequently, thirty Cuban posters. Based on this information, it was possible to understand the measures taken by the government regarding the graphic communication in Cuba, so that it would be possible to compare with other countries that were or were not under a similar regime to the Cuban, seeking similarities or differences between them, in order to confirm if the environment has made this change possible. The fundamental theoretical basis of this research uses the concepts of media theory and cultural environment of Norval Baitello Jr. and the studies of violence of the social symbols of Harry Pross